Wind resource assessment : a practical guide to developing a wind project - Brower, Michael, 1960-; Bailey, Bruce H. (Hoboken, N.J. : Wiley, 2012)
This is a practical, authoritative guide for the most important phase in developing a wind energy project."
5. Installation of Monitoring Stations5.1 Equipment Procurement; 5.2 Equipment Acceptance Testing and Field Preparation; 5.2.1 Acceptance Testing; 5.2.2 Field Preparation Procedures; 5.3 Installation Team; 5.4 Safety; 5.5 Determination of True North; 5.6 Tower Installation; 5.6.1 New Tilt-Up Towers; 5.6.2 New Lattice Towers; 5.6.3 Existing Towers; 5.7 Sensor and Equipment Installation; 5.7.1 Anemometers; 5.7.2 Wind Vanes; 5.7.3 Temperature and Other Sensors; 5.7.4 Data Loggers and Associated Hardware; 5.7.5 Sensor Connections and Cabling; 5.7.6 Grounding and Lightning Protection.
Includes bibliographical references and index.
Keywords: Wind power; Wind power plants; Power resources; Winds -- Speed; Mechanical engineering; Engineering; Electrical engineering; TECHNOLOGY & ENGINEERING -- Power Resources -- General; Wind power; Wind power plants; Electronic books; Electronic books